Si EMIL (Electric Maternity Belt) Untuk Monitoring Kesejahteraan Janin Dan Ibu Hamil 0-9 Bulan - Purwaningsih, Heni; Nurul Istiqomah; Eko Nugroho; Tria Puspitasari; Hery Siswanto (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
Electric Maternity Belt for monitoring fetal and pregnant women well-being project is an initiative aimed at addressing the issue of inadequate fetal health monitoring in remote or underserved areas. Many expectant mothers face challenges in accessing timely prenatal care, which increases the risks of complications during pregnancy. This project developed an innovative, affordable, and easy-to-use maternity belt equipped with sensors to monitor the fetal heart rate, movement, and uterine contractions, providing real-time data to healthcare providers. The method involves collaboration with local health centers to test and refine the prototype. The maternity belt was introduced to rural clinics and tested on a sample of pregnant women, with training sessions for healthcare staff on how to operate the device. The results showed that the device successfully detected fetal abnormalities, allowing for early intervention and reducing maternal anxiety. Moreover, it contributed to the improvement of healthcare access by enabling remote monitoring, even in areas with limited medical resources. The primary output of this project is a functional prototype that can be mass-produced and distributed to remote areas, helping to ensure the safety of both mother and baby. The project’s contribution lies in its ability to bridge the gap between modern healthcare technology and rural communities, providing an affordable, efficient, and reliable solution for maternal and fetal health monitoring.